Examining the relationship between child holiday club attendance and parental mental wellbeing - Michael A. Long; Paul B. Stretesky; Eilish Crilley; Zeb Sattar; Margaret Anne Defeyter (Elsevier, 2021)
Objectives: This paper reports results of an evaluation of 17 holiday clubs located throughout North East England that ran during the summer of 2017, designed to reduced summertime food insecurity. Study design: Questionnaire administed to parents/caregivers of children who attended a holiday club. Methods: Ordinary Least Squares regression models were used to predict Warwick-Edinburg Mental Wellbeing scale scores measuring parental mental wellbeing. Results: We find that after a summer of attending a holiday club, the most important factor associated with higher parental wellbeing scores is the reduction in social isolation and increased relationships that the parent and their children build while children attend holiday clubs. Conclusions: Our results suggest that reducing social isolation for parents and families during summertime is a likely a latent function of holiday clubs. These are important findings in that the benefits of holiday club appear to extend beyond access to food and reductions in household food insecurity.